NILAI-NILAI KEHIDUPAN PADA NOVEL MOGA BUNDA DISAYANG ALLAH KARYA TERE LIYE - Lozi Septiana; Yayah Chanafiah; Amril Canrhas (Jurnal Korpus, 2017)
This study aims to determine the values of life contained in the novel Moga Bunda Disayang Allah by Tere Liye. The formulation of this research problem is how the value of life contained in the novel Moga Bunda Disukai Allah by Tere Liye. The method used is descriptive. The research approach used in this study is an objective approach, focusing on intrinsic analysis. The source of this research data is the novel Moga Bunda Disayang Allah Tere Liye's work with data taken in the form of texts from the story line, theme and story, character and characterization , Point of view, the novel style of Moga Mother Dear Mother God by Tere Liye.Research Results Values of life contained in the novel Moga Mother Dear God is, judging from the main character of Bunda HK who is very fond of his disabled son and he endlessly fight against the disease Melati. Rough corals in caring for Jasmine, ugly physical but noble heart. Mr. HK is rich but inhuman, misjudging someone from his physical appearance, it turns out HK is wrong. The reef that was ostracized because of his appearance turned out to be the one who saved his daughter. Judging from the depressed Melati characters, the prestation with its limitations, suddenly can pray for Mother "met bobo Mother. Moga Mother Dear God".